Global Warming Has Imbalance Impact on Soil Nitrogen Transformation Rates - Di Zhao; Jie Qiu; Zhen Fan; Chaopu Ti; Zelin Huang; Xiaoyuan Yan; Yongqiu Xia (Earth's Future)
Abstract Global warming is projected to significantly influence soil nitrogen (N) transformations, yet a comprehensive understanding of the spatial distribution of these effects and the underlying driving factors at a large scale remains limited. This study employs a Random Forest model to develop nonlinear temperature sensitivity (Q10) models for soil nitrogen mineralization (Nmin), nitrification (Nnit), and denitrification (Nde) based on a data set comprising 1,131 records from across China. Our results revealed variations in Q10 values across different N transformation processes and ecosystem types, with an average of 1.96 for Nmin, 1.90 for Nnit, and 2.19 for Nde. Higher Q10 values (>2) for N transformation rates were observed in the Northern and Western China, which exhibited a geographical spatial pattern that changed with longitude, latitude, and altitude. Soil substrate availability, N input, soil pH and climatic variables accounted for most of the variation in Q10 among diverse ecosystem types and regions on a large scale. In projected future warming scenarios, it is expected that N transformation rates could increase by between 0.001 and 1.87 times under SSP2‐4.5 and SSP5‐8.5 from 2040 to 2100, compared to 2030. These findings deepen our understanding of the large‐scale spatial variations and controlling factors of N transformation rates in response to global warming, providing a robust foundation for more informed ecosystem management and environmental policy decisions.